Features of quantitative EEG in children with hyperkinetic disorder - R F Gasanov; I V Makarov; D A Emelina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
At the basis of numerous mental disorders lies a synaptic transmission impairment that causes metabolic and ionic changes and affects the current functional state of the brain, the reflection of which we find in electroencephalographic examination.Objective of the study: identification of electroencephalographic features in children under conditions of biochemical heterogeneity of hyperkinetic disorder (HD).Material and methods. 404 children aged 6-8 years with HD were divided into three subgroups according to the state of monoamine activity: the 1-st subgroup with a combination of hypofunction of the dopaminergic and hyperfunction of the noradrenergic systems — 120 children, the 2-nd subgroup with a combination of hyperfunction of the noradrenergic system with relative balance dopamine — 136 children, and the 3-d with a combination of hyperfunction of the dopamine and hypofunction of the noradrenergic systems — 148 children. In the selected groups, the serotonin system plays an inhibitory and modulating role in relation to the catecholamine metabolism systems. The control group consisted of 90 children (54 boys and 36 girls). An electroencephalographic study was carried out, where the following ranges and subranges were differentiated: theta rhythm (4–8 Hz) and beta1 rhythm (14–20 Hz). The power ratios of theta — and — beta1 rhythms (theta/beta1) were calculated.Results. It was the serotonin system that turned out to be the determining factor in the neurophysiological characteristics of HD. Moreover, the division into subgroups, based on the biochemical characteristics of children with HD, did not allow us to obtain significant differences. The only feature that globally distinguishes the subgroups from each other was the increase in the theta/beta1 activity index, corresponding to an increase in the tension and activity of the serotonin system from subgroup 1 to 3. The data obtained allow us to assert that the electroencephalographic index theta / beta1 can serve as a marker of inattention in children with hyperkinetic disorder and reflects the established state of imbalance of all monoamine systems, but better characterizes the behavior of the tryptophan system.Conclusion. The data on the relationship between the power of theta/beta1 rhythms in the EEG may indicate the nature of the activity of the serotonin system in prospective studies, providing a personalized approach to the selection of drug therapy in children with HD.